In this digital age, how easily accessible is pharmacist vaccination information? The case of New Zealand - Georgia Bell; Shekiba Ikhtiari; Ashley Johns; Devin Teoh; Shane Webber; Patti Napier; Mudassir Anwar (Elsevier, 2021)
Background: Pharmacist-led vaccination that has the potential to ease the vaccination burden from general practitioners, is comparatively a newer service in New Zealand. However, to reap the maximum benefits out of this service, a consistent and effective promotion approach using various online platforms is indispensable. Objective: To identify what online information the general public can find about which pharmacies across NZ provide vaccination services. Methods: Every pharmacy in NZ was reviewed online to determine what vaccination information they advertised, then a sample of pharmacies were randomly selected from six District Health Boards (DHBs) to be called and confirm if the information they stated online was accurate. Results: Whilst the majority (more than 70%) of pharmacies did provide information about their services online, only 31% of the pharmacies had vaccination information on their websites, 20% on Healthpoint, and 13% had the information on social media. The telephonic survey revealed various information discrepancies in more than a quarter of the sample. Conclusions: A lack of online presence across multiple pharmacies is a pressing issue. Also, currently, NZ pharmacies do not have a very high online presence advertising vaccination services. Improving the amount and quality of this information is pertinent at this time as when COVID-19 vaccination drive may commence anytime, and the pharmacy sector will be well placed to conduct vaccinations on a large scale.